BIODEGRADATION OF DIESEL AND CRUDE OIL USING Corynebacterium sp AND Lysinobacillus fusiformis 5B STIMULATED WITH BIOSURFACTANT, BIOCHAR AND IRON OXIDE NANOPARTICLES - Mordecai GANA; Clement Shina OLUSANYA; Agnes Dabi SHABA; Binta Buba ADAMU; Abdullahi Dabban IDRIS (Covenant Journal of Physical and Life Sciences, 2021)
Petroleum oil and its processing product are the most common anthropogenic contaminants. It contains many compounds that pose a significant risk for the environment and human health and have cytotoxic, mutagenic, and carcinogenic effects. This study was conducted to determine diesel biodegradation using Corynebacterium xerosis and crude oil using Lysinibacillus fusiformis 5B stimulated with biochar, biosurfactant, and iron oxide nanoparticle. The isolate was grown on a minimal salt medium (MSM) with diesel and crude oil as the carbon source. The test organisms were screened for the ability to utilise diesel and crude oil as sole carbon and energy source by inoculation into MSM containing 0.4 g/L of NH4Cl, 1.2 g/L of KH2PO4, 1.8 g/L of K2HPO4.3H2O, and trace amounts of 0.2 g/L of MgSO4.7H2O, 0.01 g/L of FeSO4.7H2O and 0.01 g/L of NaCl. The biodegradation studies were done using five conical flasks collectively with MSM (18 mL), isolate (2 mL), biochar (100 mg), crude oil (2 mL), biosurfactant (100 mg), and Iron oxide nanoparticles (FeONp)7 (100 mg). A control was set up without the isolate. The biodegradation was observed for 20 days, and the rate of biodegradation was determined by the weight loss method at 5 days interval. The colony-forming unit also determined microbial growth. The test organisms could utilise diesel and crude oil as their carbon source. The highest percentage biodegradation for Corynebacterium species was obtained on day 20 (86%). The un-inoculated control had 12 %. There was a gradual increase in the counts of the isolate from 4 × 106 CFU ml-1 (day 0) to 192 ×106 CFU ml-1 (day 20), Lysinobacillus fusiformis 5B gave an increase in biodegradation from 15.25 % at day 0 to 36.95 % at day 20. At the same time, the control had 12.15 % and 35.05 %, respectively. The microbial count also increased from 1.8x105 CFU/mL at day 0 to 3.8x105 CFU/mL at day 20. This study showed that Corynebacterium sp could utilise diesel, and Lysinibacillus fusiformis 5B utilised crude oil, which can be used to biodegrade petroleum-contaminated environments.